Pengaruh Pemberian Kompres Jahe untuk Mengurangi Nyeri Punggung pada Ibu Hamiltrimester III di Kota Malang - Ary Lukmana; Tut Rayani Aksohini Wijayanti; Raden Maria Veronika Widiatrilupi (Jurnal Syntax Admiration, 2024)
The purpose of the study was to determine the effect of giving ginger compresses to reduce back pain in third trimester pregnant women at PMB Bd. Sumariyah Str. Keb. Cemoro Kandang Kedungkandamg Malang City. This type of research is quantitative research. This study used a one group pretest posttest design approach. Using an experimental method with the type of research used preexperimentally, using the Numeric Rating Scale (NRS) pain scale and the instruments used are SOP for Ginger Compress and Questionnaire Sheet. This research was conducted at PMB Bd. Sumariyah S.Tr. Keb Cemorokandang. PMB Bd.Sumariyah S.Tr. Cemorokandang District, Kendungkandang District, Malang City, East Java. The results of the analysis showed a significant difference between before and after the Red Ginger Compress action, with a p-value of 0.002. In conclusion, Red Ginger Compress can effectively reduce back pain in third trimester pregnant women at PMB Sumariyah S.Tr.Keb Cemorokandang Kedungkandang Malang City.